Penerapan Model TAI untuk Meningkatkan Kemampuan Kerjasama dan Hasil Belajar Matematika Materi Barisan dan Deret Kelas IXC SMP Negeri 4 Sumbang Semester 2 Tahun Pelajaran 2017/2018 - Theresia Warsini (AlphaMath : Journal of Mathematics Education, 2019)
The problem that underlies this research is the lack of collaboration and mathematics learning outcomes of students of class IX C of SMP N 4 Sumbang. This can be seen if students have difficulty in understanding the material, students tend to be quiet and do not want to cooperate with friends, even though the cooperation of students is very necessary to achieve the success of teaching and learning. To create student cooperation in the learning process, a learning model is needed. One such learning model is the TAI (Teams Assisted Individualization) type of cooperative learning model, where the model is oriented towards collaboration, both mentally, attitudes, and socially. The purpose of this research is to find out the improvement of cooperation and learning outcomes in mathematics through the application of cooperative learning models in the form of sequence and series TAI material. This research is a Classroom Action Research. Learning tools, namely syllabus, lesson plans, teaching materials, and worksheets. While the research instrument is the description test and observation sheet. The subjects of the study were 22 students of the IXC class at SMPN 4 Sumbang. Data sources come from teachers and students. Data collection techniques are by observation, and tests. The study was conducted in December 2017 until April 2018. The subject and time of the study were chosen because the researcher taught in the class and the implementation time was adjusted to the lesson schedule. The research procedure begins with problem identification, action planning, implementation of actions and observations, and analysis and reflection. The results showed that the ability of student cooperation, from the first cycle the percentage of student cooperation with the category of "quite good" 27% and the category of "good" by 73% to the category of "good" 54% and the category of "very good" by 45% in the second cycle. Student learning outcomes in the first cycle obtained an average of 72.18 with a classical completeness of 59.09% and an increase in the second cycle an average value of 80.36 with a classical completeness of 81.82%. From these results it is recommended that teachers be able to clarify the process of assessing the ability of students to collaborate in the learning process, so that the implementation of learning can run smoothly. While students are advised to increase collaboration so that individual and group learning outcomes can be achieved to the maximum.